Slowed Saccadic Reaction Times in Seemingly Normal Parts of Glaucomatous Visual Fields - Thepass, Gijs; Lemij, Hans G.; Vermeer, Koenraad A.; van der Steen, Johannes; Pel, Johan J. M. (Frontiers in Medicine, 2021)
Purpose: In eye movement perimetry, peripheral stimuli are confirmed by goal-directed eye movements towards the stimulus. The saccadic reaction time (SRT) is regarded as an index of visual field responsiveness, whereas in standard automated perimetry (SAP), the visual field sensitivity is tested. We investigated the relation between visual field sensitivity and responsiveness in corresponding locations of the visual field in healthy controls and in patients with mild, moderate and advanced glaucoma. Materials and methods: Thirty-four healthy control subjects and 42 glaucoma patients underwent a 54-point protocol in eye movement perimetry (EMP) and a 24-2 SITA standard protocol in a Humphrey Field Analyzer. The visual field points were stratified by total deviation sensitivity loss in SAP into 6 strata. A generalized linear mixed model was applied to determine the influence of the various factors. Results: The generalized linear mixed model showed that the mean SRT increased with increasing glaucoma severity, from 479 ms in the control eyes to 678 ms in the eyes of patients with advanced glaucoma (p<0.001). Mean SRTs significantly increased with increasing SAP sensitivity loss. Even at the locations where no sensitivity loss was detected by SAP (total deviation values greater or equal than 0 dB), we found lengthened SRTs in mild, moderate and advanced glaucoma compared to healthy controls (p<0.05) and in moderate and advanced glaucoma compared to mild glaucoma (p<0.05). At locations with total deviation values between 0 and -3dB, -3 and -6dB and -6 and -12dB, we found similar differences. Conclusions: The lengthened SRT in areas with normal retinal sensitivities in glaucomatous eyes, i.e., planning and execution of saccades to specific locations, precede altered sensory perception as assessed with SAP. Better understanding of altered sensory processing in glaucoma might allow earlier diagnosis of emerging glaucoma.